Nm23 and HER2/neu gene expression and prognostic significance in urothelial carcinomas of the bladder (Annals of Medical Research, 2021)
Aim: This study aimed to investigate the expressions of Nm23-H1 and HER2/neu in Turkish cases of urothelial carcinomas of bladder and to examine their associations with prognostic parameters. Urothelial carcinoma of the bladder is one of the most prevalent cancers worldwide. Nm23-H1 and HER2/neu expressions have been previously studied in urothelial carcinomas. Despite the availability of many reports in the literature, the prognostic significance of these expressions remains unclear.Materials and Methods: Fifty cases of urothelial carcinoma of the bladder treated with radical cystectomy were retrospectively reviewed. The tumor specimens were evaluated by immunohistochemistry using Nm23-H1 and HER2/neu antibodies.Results: Immunohistochemically, Nm23-H1 and HER2/neu expressions were present in 80% and 18% of cases and associated with pathological stage (p=0.025 and p=0.023, respectively).Conclusion: Both antibodies were noted in patients with advanced stage cancer, which can adversely affect prognosis in infiltrativeurothelial carcinomas of the bladder. HER2/neu may be a target for therapy.